Memorable wellness tourism experiences: antecedents that lead to enjoyable outcomes - Brian Garrod (International Journal of Spa and Wellness, 2025)
Wellbeing is a popular tourism motivation, and wellness tourism is a growing market segment in many places around the world. Contrary to existing studies replicating Kim et al.’s (2012) seven-dimensional memorable tourism experience scale (hedonism, refreshment, local culture, meaningfulness, knowledge, involvement, and novelty) in new settings, this study uses stimulus–organism–response (S-O-R) theory as a conceptual foundation to develop and test an integrative model of memorable tourism experiences within the context of wellness tourism. Escapism, co-creation, experience intensification and satisfaction are taken as potential antecedents of memorable wellness tourism experiences, while hedonic well-being, eudaimonic well-being and place attachment are considered potential consequences. A survey was conducted to gather data from Chinese tourists over the age of 18 years who had a wellness tourism experience during the period February to July 2024. The empirical results suggest that the greater the level of escapism, co-creation, experience intensification and satisfaction, the more memorable the wellness tourism experience; while a more memorable wellness tourism experience will lead to greater hedonic well-being, eudaimonic well-being and place attachment. This study concludes by discussing the theoretical and managerial implications of the findings, while providing recommendations for future research.